INTER-ETHNIC SOCIAL INTERACTION FOR MULTICULTURAL EDUCATION STUDY IN THE COMMUNITY OF BAYAR JAYA VILLAGE - Rajagukguk, Jontar (CV. Mitkom Indotama, 2025)
The purpose of this study is to find out the form of social interaction between Malays, Javanese and Karo, to find out the influence of social interaction between Malays, Javanese and Karo on conflict prevention in Bayar Jayavillage and also to find out the influence of social interaction between Malays, Javanese and Karo about conflict prevention in Bayar Jayavillage. inter-tribal government. social interaction in the prevention of ethnic conflicts in Tambang Jaya Village, Bahorok District. This type of research is qualitative descriptive research. Data collection techniques include interviews, documentation and observation. The data analysis technique used is qualitative descriptive. The results of this study show that the forms of social interaction between the Malay, Javanese and Karo tribes in Bayar Jayavillage are cooperation, competition, accommodation and assimilation. Among the Malays, Javanese and Karo tribes, the forms of cooperation that can be seen are social cooperation and cooperation. The form of competition can be seen from economic competition and competition in the administrative field. A form of settlement that can be seen from the existence of settlements and inter-ethnic practices in Bayar Jayavillage, Bahorok District. And this form of assimilation can be seen in the use of colloquial language between tribes in Bayar JayaVillage, Bahorok District. Social interaction between ethnic Malays, Javanese and Karos has social effects, namely positive effects that cause cooperation and negative effects that cause conflict or conflict. The government has a very important role in suppressing and resolving confusion that may arise from conflict through negotiation, mediation and mentoring.